Fiber nonlinear predictive model for combined bending-compression loading of an orthogonal plane weave composite laminate structure. (December 2014) - Guo, Siming; Gresil, Matthieu; Sutton, Michael; Deng, Xiaomin; Reifsnider, Kenneth W; Majumdar, Prasun
To increase understanding of damage evolution in advanced composite material systems, a series of large deflection bending-compression experiments and model predictions have been performed for a woven glass-epoxy composite material system. Theoretical developments employing both small and large deformation models and computational studies are performed. Results (a) show that the Euler–Bernoulli beam theory for small deformations is adequate to describe the shape and deformations when the axial and transverse displacement are quite small, (b) show that a modified Drucker's equation effectively extends the theory prediction to the large deformation region, providing an accurate estimate for the buckling load, the post-buckling axial load-axial displacement response of the specimen and the axial strain along the beam centerline, even in the presence of observed anticlastic (double) specimen curvature near mid-length for all fiber angles (that is not modeled), and (c) for the first time the quantities σeff – ɛeff are shown to be appropriate parameters to correlate the material response on both the compression and tension surfaces of a beam-compression specimen in the range 0 ≤ ɛeff < 0.005 as the specimen undergoes combined bending-compression loading. In addition, computational studies indicate that the experimental σeff – ɛeff results are in reasonable quantitative agreement with unwoven laminate finite element simulation predictions in the range 0 ≤ ɛeff < 0.010, with the effect of the woven structure appearing to provide the key constraint for various fiber angles that leads to the observed consistency in the experimental σeff – ɛeff results on both surfaces.